The Weight of HLA-DPA1 rs3077 Single Nucleotide Polymorphism in Prostate Cancer, a Multicenter Study. (22nd April 2021) - Alenzi, Mohammed Jayed; Ghazy, Amany A.; Taha, Diaa-Eldin
Abstract : Prostate cancer (PCa) has almost the highest genetic transmission that mimics an autosomal dominance hereditary pattern of cancers in some families. Its incidence in Arab countries was reported to be steadily increasing. Aim . To determine the relevance of HLA-DPA1 rs3077 (A/G) SNP with prostate cancer's risk and/or severity. Subjects and Methods . Forty PCa patients and forty age matched patients with benign prostatic hyperplasia (BPH), as a control group, were enrolled in the study. Serum levels of urea, creatinine, total prostate-specific antigen (PSA), and free PSA were measured. PSA ratio was determined as well. Genotyping of HLA-DPA1 rs3077 (A/G) SNP was done using real-time PCR. Results . The measured lab parameters, except free PSA, were significantly higher among PCa patients in comparison to controls (P < 0.001 ∗ ). Moreover, PSA ratio was significantly high among PCa patients (P < 0.001 ∗ ). HLA-DPA1 rs3077 GG genotype was more frequent in PCa patients and the associated OR was 2.546 (P = 0.059 ), while AA genotype was more frequent in the control group and the associated OR was 0.145 (P = 0.081 ). Frequency of G allele was higher among PCa patients than the control group while A allele frequency was significantly decreased (P = 0.034 ∗ ) (protective allele). On multivariate analysis, there is no significant correlation found between HLA-DPA1 rs3077 SNP and PSA ratio (OR = 4.5, 95% CI = 1.2–17.4, P = 0.856 ). Conclusion . HLA-DPA1 rs3077 G allele could be a risk factor for prostate cancer. However, HLA-DPA1 rs3077 SNP has no relation to PCa severity.